The application of impact counseling in therapy started with individual counseling expressive to cope with the personal problems by college students - Syahniar, Syahniar (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
Various approaches and theory can be applied to help students to cope with personal problems; one approach that can be applied is the impact counseling. Impact Therapy is a teaching process that carried out by the counselor, where a counselor wrote and visualized to clients about what the client wants, the client will do, how clients assess their behavior and how clients to plan what to do next. This is illustrated by Ed Jacobs As WDEP (Want, Doing, Evaluate, and Plan). Before using the impact counseling for students who are not able to communicate the problems that they experienced first counselor implemented expressive therapy. Expressive therapy known as a therapy in counseling and psychotherapy in which the client can communicate and express its feelings and their thoughts through activities related to art, music, dance, drama, poetry, as well as games. Expressive therapy is also called the